Adaptation of the Global Motivation Scale (GMS-28) in Indonesian Version - Anissa Cessarea; Urip Purwono; Asteria Devy Kumalasari (PT Mattawang Mediatama Solution, 2023)
Motivation is one of the important variables for study, whereas many motivational studies have been conducted to predict learning, performance, and behavior change. The motivational scale that has gone through psychometric testing is required in motivational research to accurately describe the construct. There is still low availability of motivational scale in Indonesia that has passed the psychometric testing. Therefore, this study aims to adapt the Global Motivation Scale (GMS-28) into Indonesian. The adaptation process refers to the adaptation guidelines by the International Test Commission, where the process of adaptation also involves psychometric testing. Data collection was carried out using an online questionnaire on 383 participants aged 18-25 years. The psychometric test was carried out using internal consistency reliability and validity based on internal structure. The internal consistency scale has revealed all acceptable reliability coefficients aspects with a range of a = 0.703 – 0.810. Item analysis pointed out that all items have good item-total correlation and item mean. Findings from First-order Confirmatory Factor Analysis showed that all aspects have acceptable model fit and all of the items significantly measures the aspects on GMS-28. Based on these results, it can be concluded that the Indonesian version of the GMS-28 is suitable for use for further studies. However, further testing needs to be done using a larger sample to be used in all Indonesian populations.